2019
DOI: 10.1073/pnas.1820245116
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2AX promotes neuronal health by controlling mitochondrial homeostasis

Abstract: Phosphorylation of histone H2AX is a major contributor to efficient DNA repair. We recently reported neurobehavioral deficits in mice lacking H2AX. Here we establish that this neural failure stems from impairment of mitochondrial function and repression of the mitochondrial biogenesis gene PGC-1α. H2AX loss leads to reduced levels of the major subunits of the mitochondrial respiratory complexes in mouse embryonic fibroblasts and in the striatum, a brain region particularly vulnerable to mitochondrial damage. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Above results indicated that ASH could induce DNA double strand breaks in HepG2 cells and trigger subsequent apoptotic cell death. When a double-strand break occurs in DNA, a sequence of events occurs in which the H2A histone family member X (H2AX) becomes phosphorylated on serine 139 [23,26]. Thus, we detected the expression of phospho-H2A.X-Ser139 and H2A.X to further confirm ASH induced DNA damage.…”
Section: Resultsmentioning
confidence: 95%
“…Above results indicated that ASH could induce DNA double strand breaks in HepG2 cells and trigger subsequent apoptotic cell death. When a double-strand break occurs in DNA, a sequence of events occurs in which the H2A histone family member X (H2AX) becomes phosphorylated on serine 139 [23,26]. Thus, we detected the expression of phospho-H2A.X-Ser139 and H2A.X to further confirm ASH induced DNA damage.…”
Section: Resultsmentioning
confidence: 95%
“…Although phosphorylation of H2AX is an initial step in DDR, the histone has also been implicated in cell proliferation and apoptosis (see Introduction), and, very recently, in the support of neuronal maintenance via controlling mitochondrial homeostasis [ 35 ]. Given the pleiotropic effects of the molecule—and considering that the links between cell proliferation and apoptosis in adult and old neurogenesis are quite complex [ 15 ]—we have split our discussion to first consider the γH2AX/cCASP3 response to irradiation, a well-established DNA damaging event, and then the presence of the two molecules in the normal aging brain.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that TMS may have induced DNA damage and consequent apoptosis in 143B cells. H2AX is phosphorylated on serine 139 and is then designated as γ H2AX in a reaction involving DNA double-strand breaks [ 24 , 25 ]. Therefore, the expression of H2AX and phosphorylation of H2AX-Ser139 were examined to confirm that treatment with TMS induced DNA damage in 143B cells.…”
Section: Resultsmentioning
confidence: 99%